Nutritional status and self-reported nutrition education exposure in women with gestational diabetes mellitus at primary health clinic / Nurul-Alia Samiun … [et al.] - Samiun, Nurul-Alia; Mohd Yusof, Barakatun-Nisak; Ismail, Irmi Zarina; Mohd Anuar, Norfarhana; Chee, Winnie Siew Swee (Universiti Teknologi MARA Cawangan Selangor, 2019)
Introduction: Optimal nutritional status is of utmost importance not only for foetal development but also to maintain normoglycemia in women with gestational diabetes mellitus (GDM). This cross-sectional study described the nutritional status of women with GDM and explored whether self-reported nutrition education (NEd) exposure before a GDM diagnosis would be able to promote better nutrition status. Methods: GDM women (n= 60; age= 31.6 ± 5.0 years) diagnosed between 13th and 28th week of gestation participated in the study. We assessed nutritional status that included anthropometric and blood pressure assessments, biochemical data, and dietary intake. The respondents self-reported their NEd exposure before a GDM diagnosis was made. Results: The pre-pregnancy BMI of the participants was 27.9 ± 6.8 kg/m2, which was categorised as overweight. Total (4.3 ± 5.6 kg) and rate (0.2 ± 0.3 kg/week) of gestational weight gain were within the recommendations. Glycemic parameters and blood pressure were also within the normal range. Nevertheless, they had high intakes of fat (35.5%) and sugar (14.4%) proportionate to their energy intake. They did not meet the recommended nutrient intakes for fibre, calcium, and iron. Only 28.3% of women had prior NEd exposure. Among them, almost all (94.1%) had recurrent GDM. Those with NEd exposure had lower pre-prandial blood glucose profiles, systolic blood pressure, and proportion of protein intake from energy than those without (p< 0.05). Conclusions: Suboptimal maternal nutritional status and low exposure to NEd are evident in women with GDM. Those with self-reported NEd exposure had better parameters of nutritional status. The findings recognised the need of having proper nutrition education for women who are at high risk of GDM since at early pregnancy.